Problem of domestic violence and its solutions in the light of Maqasid Shariah - Muhammad Husni, Ahmad; Nasohah, Zaini; Mohd Kashim, Mohd Izhar Ariff (Canadian Center of Science and Education, 2015)
The spread of family problems in the contemporary period leads to divorce and family disengagement in society; the study revolves around the emergence of social problems resulting from wife’s work outside home which makes her neglects her certain rights and obligations. Moreover, cases of domestic violence have increased such as beating and verbal abuse in all its forms. Accordingly, the study lies in building a happy family which is the first nucleus of society whose integrity and corners must be protected, and also highlights the role of maqasid shariah in solving problems of modern family; thus, the study aims at highlighting the rights and obligations between spouses in accordance with Islamic law, and to identify the reasons and motivations that lead to the existence of these problems and how to solve them from the maqasid shariah perspective. The study adopted the inductive and analytical approach and looked into schools of Islamic jurisprudence, and discussed the views of the jurists through explaining their authorities in the issue, and discussed the points of agreement and disagreement, and then analyzed the texts and issues in the light of maqasid shariah. The result shows that the main reason for having family problems is the lack of knowledge of the spouses with rights and obligations and abiding by them. And that wife’s work is permitted within limits and restrictions that are not contrary to maqasid shariah, and a working wife has to balance between her work and paying attention to family matters, and it also shows that domestic violence within the family is contrary to maqasid shariah that is based on love and compassion between the couple and that occurs as a result of ignorance of the shariah secret in building a family; and it is compulsory on each of them to abide by the shariah teachings and stick to its maqasid (purposes) and to implement them in the family life, and with this, family life will last in the obedience of Lord Allah (swt).